Factors influencing osteoradionecrosis progression during hyperbaric oxygen therapy: A case study [version 2; peer review: 1 approved, 2 approved with reservations] - Khadija Bahrini; Chaima Zitouni; Sameh Mezri; Hedi Gharsallah; Wiem Boughzala; Mounir Haggui (F1000Research)
Introduction Although relatively uncommon, osteoradionecrosis (ORN) remains a serious complication following radiotherapy. Various therapeutic approaches, including hyperbaric oxygen therapy (HBOT), are utilized in managing ORN. This study aims to evaluate the role of HBOT in ORN management and to identify predictive factors influencing the evolution of head and neck ORN after HBOT. Methods This retrospective study includes 46 patients who received HBOT for head and neck ORN between 2017 and 2020. The patients were divided into two groups: Group 1 (n=36) included those with regression or stabilization of ORN, while Group 2 (n=10) comprised patients with worsening lesions. We performed a statistical study in order to identify factors influencing ORN progression under treatment. Results ORN affected the mandible in 93.5% of patients, the maxilla in 2 cases, and the skull base in 4 cases. All patients received HBOT, with an average of 44.65 sessions. Pre-operative HBOT was administered in 17% of cases, and post-operative HBOT was given in 42% of cases. After at least 20 sessions, ORN regressed in 33% of cases, stabilized in 45%, and worsened in 22%. Analysis of factors influencing ORN progression on the univariate study revealed significant associations with high blood pressure (p=0.046), larger tumor size (p=0.004), advanced tumor stages (p=0.048), mean radiation dose (p=0.002), delays between dental care and radiotherapy (p=0.045), and the location of ORN within the mandible (p=0.049). Additionally, the number of HBOT sessions significantly affected ORN evolution, with more sessions correlating with better outcomes (p=0.001). In the multivariate analysis, variables such as the average interval between dental care and radiotherapy (p=0.043) as well as the number of HBOT sessions (p=0.040) emerged as significant influencers of ORN evolution. Conclusion Our study provides valuable insights into the management of ORN by identifying key predictors that influence the post-therapeutic evolution of head and neck ORN after HBOT.